Blood Product Administration During the Role 1 Phase of Care: The Prehospital Trauma Registry Experience. Issue 1 (4th January 2022) - Fisher, Andrew D; Paulson, Matthew W; McKay, Jerome T; Bynum, James; Flarity, Kathleen M; Howell, Michelle; Bebarta, Vikhyat S; Schauer, Steven G
ABSTRACT: Background: The majority of combat deaths occur in the prehospital setting. Efforts to increase survival including blood transfusions are made in the prehospital setting. The blood products available in the Role 1 setting include whole blood (WB), red blood cells (RBCs), fresh frozen plasma (FFP), and lyophilized (freeze-dried) plasma (FDP). Methods: This is a secondary analysis of a previously published dataset within the Prehospital Trauma Registry (PHTR) from 2003 through May 2019. Deterministic linking was used when possible with the DoD Trauma Registry for outcome data. Descriptive statistics were used to analyze the data. Results: We identified 1, 357 patient encounters in the PHTR. Within that group, 28 patients received a prehospital blood product, with 41 total administrations: WB (18), RBCs (12), FFP (6), FDP (3), and blood not otherwise specified (2). Outcome data were available for 17 of the 28 patients. The median injury severity score was 20, with the thorax being the most frequent seriously injured body region. Most (94%) patients survived to discharge. The median ICU days was 11 (Interquartile Range [IQR] 3-19), and the median hospital days was 19 (IQR 8-29). The average volume (units) of RBCs was 6.0 (95% CI 1.9-10.1), WB 2.8 (95% CI 0.0-5.6), platelets 0.7 (95% CI 0.0-1.4), and FFP 5.0 (95% CI 1.2-8.8). Conclusions: The use of prehospital blood products is uncommon in U.S. combat settings. Patients who received blood products sustained severe injuries but had a high survival rate. Given the infrequent but critical use and potentially increased need for adequate prolonged casualty care in future near-peer conflicts, optimizing logistical chain circulation is required.